Pola Penyakit Infeksi Menular Seksual di Poliklinik Kulit dan Kelamin RSP Bintang Amin Periode 2 Januari 2016 – 31 Desember 2020 - Arif Effendi; Eka Silvia; Syafei Hamzah; Muhammad Alkabir Ridhwan (Puslitbang Sinergis Asa Professional, 2021)
Sexually Transmitted Infections (STIs) are infections that are spread primarily through sexual contact. More than 30 types of microorganisms are known to be transmitted through sexual contact. The most common infections include gonorrhea, chlamydia, syphilis, trichomoniasis, hepatitis B, genital herpes, and human papillomavirus (HPV) infection. Some of the factors that may contribute to the incidence of STIs are sociodemographic and behavioral factors. Purpose: To find out the pattern of sexually transmitted infections at the Skin and Venereal Polyclinic of Bintang Amin Hospital for the period of January 2, 2016 - December 31, 2020. Research Methods: Quantitative descriptive study and cross sectional design and total sampling technique using a questionnaire. Results: The number of samples was 51 from 51 populations, the pattern of sexually transmitted infections in the Polyclinic of Skin and Sex at RSP Bintang Amin, namely condyloma acuminata as many as 28 people (54.9%), candidiasis as many as 16 people (31.4%), Herpes simplex as many as 4 people (7.8%), syphilis as much as 2 people (3.9%) and the lowest was Gonorrhea 1 person (2.0%). Conclusion: The prevalence of sexually transmitted infections that most often occurred in the Skin and Gender Polyclinic of Bintang Amin Hospital for the period January 2, 2016 - December 31, 2020, was obtained the most, namely condyloma acuminata as many as 28 patients (54.9%), with the most female sex being 40 patients ( 78.4%). Age 25-49 years were 36 patients (70.6%), and those who were married were 46 patients (90.2%).